Development of an audio watermarking with decentralization of the watermarks - Amita Singha; Muhammad Ahsan Ullah (Journal of King Saud University: Computer and Information Sciences)
In this paper, a digital watermarking technique for ensuring security to an audio signal is presented. The proposed technique is developed by using discrete wavelet transform (DWT) and singular value decomposition (SVD). The proposed technique is executed by incorporating multi-level DWT along with the use of multiple images with different sizes as watermarks. The proposed technique is developed by keeping in mind the distribution of watermark signals’ energy throughout the entire host signal i.e. the watermarks are decentralized over the entire region of the host signal. The proposed technique is robust as experimentally the proposed technique offers PSNR (Peak Signal to Noise Ratio) of 196.8105 dB and normalized cross-correlation (NCC) over 0.9.